Balik Nama Pada Sertifikat Yang Mengandung Unsur Perbuatan Melawan Hukum - Dwi Laksa Marabintang; Andi Suriyaman M. Pide; Muhammad Ilham Arisaputra (Widya Yuridika, 2022)
This study uses empirical research methods, by analyzing the data collected through interviews and literature studies, then analyzed qualitatively and presented descriptively. The results show that the responsibility of the Land Office in this case the South Jakarta City Administration Land Office is to receive reports from the original owner of the land title certificate whose land has been transferred to a prospective buyer with a fake PPJB made by a fake PPAT so that an illegal act is indicated. The Land Administration of South Jakarta City then checks the validity of the transfer process as a responsibility in the event of a dispute or conflict over land rights, then accepts the request for cancellation of the land rights certificate which begins with blocking the certificate for 30 (thirty) days. Furthermore, the legal protection of the owner of the certificate by the Land Office of the City of South Jakarta Administration then blocked the certificate of land rights based on physical data and juridical data owned by the applicant, because the mortgage has been charged by the Nusantara Savings and Loans Cooperative. If done by the seller, the debt will be charged to the buyer, then the South Jakarta Administrative City Land Office records every legal action taken by the applicant in the land book certificate in question and conducts a field title to review the location of the disputed object and then the results will be submitted to the South Jakarta BPN Regional Office. to issue a Certificate of Cancellation of Certificate then the certificate will be crossed out and returned to the original owner